“Detection and characterization of fractures in the Eocene Thebes formation using conventional well logs in October field, Gulf of Suez, Egypt” - M. Gamal; A.A. El-Araby; A.N. El-Barkooky; Alaa Hassan (Egyptian Journal of Petroleum)
Fractures are one of the most prevalent and important geological features in petroleum exploration and production, as they have a substantial impact as conduits for hydrocarbon flow and improve the overall permeability of the formation. Despite their necessity, detecting and characterizing natural fractures still represents a difficult challenge. This study provides a technique for detecting and characterizing naturally fractured reservoirs using conventional well logs in the Eocene Thebes Formation, October Field, Gulf of Suez. Especially as this technique is not applied widely in October Field or even in the Gulf of Suez. Most carbonate reservoirs are complex and heterogeneous; one of the reasons is their naturally fractured characteristics. These fractures can significantly affect reservoir behavior, performance, and production. Despite being the most commonly available data source, logs are rarely employed in a systematic way to have a complete quantitative analysis of naturally fractured reservoirs. Since the presence of fractures affects all well logs in one way or another. This study presents an integrated workflow for determining fracture presence potentiality by combining conventional well logs, thin sections, and other available data in absence of directly advanced logging technologies such as Formation MicroImager (FMI), Dipole Shear Image (DSI), and Borehole Televiewer (BHTV). This integrated workflow was very effective and useful in the evaluation of potential fractures' existence, reservoir characterization, and development. Finally, the results of this integrated workflow suggest a high probability of fracture existence and identification in Thebes Formation, confirming that integration between conventional logging and other available data is very precious, and has a good potential to be used in absence of direct advanced methods for fractured reservoir characterization. For further studies, core data and advanced logs would be beneficial for correlation, since they would provide a more accurate picture of the fracture parameters.